2013
DOI: 10.1371/journal.pone.0059470
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Lactobacillus curvatus HY7601 and Lactobacillus plantarum KY1032 in Diet-Induced Obese Mice Is Associated with Gut Microbial Changes and Reduction in Obesity

Abstract: ObjectiveTo investigate the functional effects of probiotic treatment on the gut microbiota, as well as liver and adipose gene expression in diet-induced obese mice.DesignMale C57BL/6J mice were fed a high-fat diet (HFD) for 8 weeks to induce obesity, and then randomized to receive HFD+probiotic (Lactobacillus curvatus HY7601 and Lactobacillus plantarum KY1032, n = 9) or HFD+placebo (n = 9) for another 10 weeks. Normal diet (ND) fed mice (n = 9) served as non-obese controls.ResultsDiet-induced obese mice treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
182
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(196 citation statements)
references
References 57 publications
11
182
1
2
Order By: Relevance
“…Manipulating the gut microbiota with probiotics may improve dysbiosis associated with an HFD. In support of this, consumption of an HFD upregulates the expression of genes involved in hepatic lipid biosynthesis, and supplementation with Lactobacillus curvatus HY7601 and Lactobacillus plantarum KY1032 upregulates the expression of genes involved in hepatic FA oxidation (57). Another study showed that increasing tissue n-3 PUFAs in the gut alters the gut bacterial composition, which is associated with a decrease in LPS and gut permeability and eventually results in metabolic endotoxemia and inflammation (95).…”
Section: Introductionmentioning
confidence: 91%
“…Manipulating the gut microbiota with probiotics may improve dysbiosis associated with an HFD. In support of this, consumption of an HFD upregulates the expression of genes involved in hepatic lipid biosynthesis, and supplementation with Lactobacillus curvatus HY7601 and Lactobacillus plantarum KY1032 upregulates the expression of genes involved in hepatic FA oxidation (57). Another study showed that increasing tissue n-3 PUFAs in the gut alters the gut bacterial composition, which is associated with a decrease in LPS and gut permeability and eventually results in metabolic endotoxemia and inflammation (95).…”
Section: Introductionmentioning
confidence: 91%
“…Rijkers et al categorised the benefit of probiotics into three levels based on location and method; (1) interference with the growth or survival of pathogenic microorganisms in the gut lumen, (2) improvement of mucosal barrier function or mucosal immune system and (3) influence beyond the gut through the systemic immune system and other organs [125]. A study undertaken by Park et al found that DIO mice treated with the probiotic strains Lactobacillus curvatus HY7601 and Lactobacillus plantarum KY1032 experienced reduced body weight gain and fat accumulation in addition to lowered plasma insulin, leptin, total-cholesterol and liver toxicity biomarkers compared to a group on the same diet supplemented with a placebo [126]. Supplementation with these probiotic strains also resulted in down-regulation of pro-inflammatory genes in adipose tissue, up-regulation of fatty acid oxidation-related genes in the liver and significant alterations in the diversity and function of the gut microbiota.…”
Section: Modulation By Probioticsmentioning
confidence: 99%
“…and Lactobacillus sp. have been reported to suppress the development of obesity (10,11), and starter (Leu. mesenteroides)-fermented kimchi has been reported to regulate adipogenesis-and lipogenesis-related genes (e.g., PPAR, C/EBP, and FAS) in obese mice (4).…”
Section: Kimchi Attenuated the Mrna Levels Of Ppar- C/ebp And Fasmentioning
confidence: 99%
“…and Lactobacillus sp. (the kimchi-derived LAB) have various physiological activities (7) and suppress the progress of obesity (10,11). The use of Leu.…”
Section: Introductionmentioning
confidence: 99%